Study on formation of vortex rings - Cho, Jia Ci. (2012)
The formation of vortex rings under different operating conditions in a still fluid environment is studied experimentally. This is done by using a piston-cylinder setup immersed in water with the use of dye-water mixture to visualize the fluid flow. The operating conditions are varied with four velocity programs and stroke ratio, L/D , between values of 2 and 8. The four velocity programs involved are the constant, positively sloped (PS) ramp, negatively sloped (NS) ramp and isosceles velocity programs. For the constant velocity program, the constant velocities of 50mm/s and 200mm/s were investigated. Therefore, there were a total of five cases. For each case, the formation number (f) was determined. It was found that for the velocity program of constant velocity 50mm/s and PS Ramp was the range closer to the range of 3.6 – 4.5 as specified by Gharib et al. [1], i.e. at a range of 4 ≤ f ≤ 5 and 3 ≤ f ≤ 4 respectively. For the velocity programs of constant velocity 200mm/s, NS Ramp and isosceles, the range was found to be 2 ≤ f ≤ 3.